The Influence of Service Quality, Tax Collection Strategies and Tax Sanctions on Taxpayers' Compliance in Paying PBB-P2 - Berliani, Fikro; Wahyuningsih, Marwa Putri Eka; Rizkiah, Shiva; Mahariza, Atika; Ambarwati, Ambarwati (CV. Publikasi Indonesia, 2025)
The purpose of this study is to determine the influence of service quality, tax collection strategies and tax sanctions on taxpayers' compliance in paying PBB-P2. The data collection technique in this study was by distributing questionnaires containing questions with alternative answers available to land and building taxpayers (PBB-P2) in Bekasi City. The sample used in the study consisted of 60 respondents. The data analysis method used was multiple liner regression analysis, research data processing was carried out using the SPSS software model version 27. The results showed that the variable of the influence of service quality obtained a t-calculated value of 2.083 > t-table of 2.002. This shows that the influence of service quality has a positive and significant effect on taxpayer compliance. The tax collection strategy obtained a t-calculated value of 0.649 < t-table of 2.002 t-calculated values was smaller than the t-table, it means that the test results showed no significant difference stating that there was no average difference between the two groups received this indicates that the tax collection strategy of the data obtained did not provide enough evidence to reject the null hypothesis at the specified confidence level On taxpayer compliance and tax sanctions, a T-Calculation value of 6,577 > T-table of 2,002 was obtained. This shows that tax sanctions have a positive and significant effect on taxpayer compliance.